2023
DOI: 10.3389/fpls.2022.1011199
|View full text |Cite
|
Sign up to set email alerts
|

PlantTribes2: Tools for comparative gene family analysis in plant genomics

Abstract: Plant genome-scale resources are being generated at an increasing rate as sequencing technologies continue to improve and raw data costs continue to fall; however, the cost of downstream analyses remains large. This has resulted in a considerable range of genome assembly and annotation qualities across plant genomes due to their varying sizes, complexity, and the technology used for the assembly and annotation. To effectively work across genomes, researchers increasingly rely on comparative genomic approaches … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 128 publications
0
15
0
Order By: Relevance
“…Gene family analysis is performed using PlantTribes2 and the pre-constructed 26Gv2-scaffold orthogroup database (Wafula et al 2022). Out of the 18,110 pre-constructed orthogroups, proteins from all apple annotations [5 published genomes (‘Honeycrisp’ (Khan et al 2022), ‘Gala’ (Sun et al 2020), ‘Hanfu’ (L. Zhang et al 2019), ‘Antonovka’ (Švara et al 2023), and the GDDH13 ‘Golden Delicious’ (Daccord et al 2017) genomes) and the ‘WA 38’ genome from this work] are found in 11,671 orthogroups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gene family analysis is performed using PlantTribes2 and the pre-constructed 26Gv2-scaffold orthogroup database (Wafula et al 2022). Out of the 18,110 pre-constructed orthogroups, proteins from all apple annotations [5 published genomes (‘Honeycrisp’ (Khan et al 2022), ‘Gala’ (Sun et al 2020), ‘Hanfu’ (L. Zhang et al 2019), ‘Antonovka’ (Švara et al 2023), and the GDDH13 ‘Golden Delicious’ (Daccord et al 2017) genomes) and the ‘WA 38’ genome from this work] are found in 11,671 orthogroups.…”
Section: Resultsmentioning
confidence: 99%
“…A full list of genomes analyzed can be found in Supplemental Table S7) following the method described by (Khan et al 2022). Briefly, predicted protein sequences from the selected pome fruit genomes were classified into a pre-computed orthogroup database (26Gv2.0) using the both HMMscan and BLASTp option implemented in the GeneFamilyClassifier tool from PlantTribes2 (Wafula et al 2022). Overlapping orthogroups among M. domestica genomes were calculated and visualized with the UpSet plot function implemented in TBtools v2.030 (Chen C., 2023).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cleaned reads were de novo assembled using Trinity ( Grabherr et al 2011 ; Haas et al 2013 ) with the default parameters. The resulting transcriptome assemblies were post-processed with the PlantTribes tool ( Wafula et al 2022 ) AssemblyPostProcessor ( https://github.com/dePamphilis/PlantTribes ) using Oryza sativa ESTScan score matrices ( Iseli et al 1999 ) to produce non-redundant sets of predicted coding sequences and their corresponding translations ( supplementary table S2, Supplementary Material online). Additional filtering was performed on post-processed assemblies to remove non-plant contaminant sequences by screening transcripts against NCBI non-redundant protein database using BLASTp ( Altschul et al 1990 ) (E-value = 1e−5) as shown in supplementary tables S13 a and S13 b , Supplementary Material online.…”
Section: Methodsmentioning
confidence: 99%
“…The Arabidopsis thaliana proteome was obtained from Phytozyme 12, and genes were sorted into the 12-genome OrthoMCL gene family circumscriptions using GeneFamilyClassifier in Plant Tribes ( Wafula et al 2022 ). Genes representing the heme and chlorophyll biosynthetic pathway, and light harvesting and photosynthetic pathways were selected following Wickett et al (2011) , and Arabidopsis gene annotations were associated with corresponding orthogroups.…”
Section: Methodsmentioning
confidence: 99%